2004
DOI: 10.2136/vzj2004.0570
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall‐Induced Soil Surface Sealing: A Critical Review of Observations, Conceptual Models, and Solutions

Abstract: Rainfall‐induced soil surface sealing can have severe agricultural, hydrological, and environmental effects. Seal formation is a complex phenomenon dominated by a wide variety of factors involving soil properties, rainfall characteristics, and flow conditions. It has been studied through extensive experimental investigations as well as simulation models. This study reviews some of the main issues, in terms of morphology, phenomenology, and both conceptual and empirical modeling approaches to improve our percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 219 publications
(37 citation statements)
references
References 119 publications
(273 reference statements)
0
35
0
2
Order By: Relevance
“…In contrast with the buffer effect of the ash layer, postfire soil surface sealing caused by direct raindrop impact can promote run‐off generation and responds rapidly to postfire rainfall (DeBano, ; Martin & Moody, ). Martin and Moody () suggested that soil surface sealing can be attributed to precipitation and run‐off, the former contributing to the development of structural crusts (Assouline, ) and the latter to depositional crusts (Onda, Dietrich, & Booker, ). Increased postfire run‐off and sediment yields in the Colorado Front Range were mainly caused by soil surface sealing rather than by changes in soil water repellency (Larsen et al .…”
Section: Wildfire Effects On Hydrological Processesmentioning
confidence: 99%
“…In contrast with the buffer effect of the ash layer, postfire soil surface sealing caused by direct raindrop impact can promote run‐off generation and responds rapidly to postfire rainfall (DeBano, ; Martin & Moody, ). Martin and Moody () suggested that soil surface sealing can be attributed to precipitation and run‐off, the former contributing to the development of structural crusts (Assouline, ) and the latter to depositional crusts (Onda, Dietrich, & Booker, ). Increased postfire run‐off and sediment yields in the Colorado Front Range were mainly caused by soil surface sealing rather than by changes in soil water repellency (Larsen et al .…”
Section: Wildfire Effects On Hydrological Processesmentioning
confidence: 99%
“…Variations in infiltration rate, soil water content, water suction, bulk density and surface roughness are all affected by raindrop impact (Fohrer et al, 1999), and this is mainly due to the formation of a surface seal that is primarily created by raindrop impacts (Assouline, 2004;Bradford et al, 1987;Mualem et al, 1993). Many studies have investigated the effects of surface seal induced variations on infiltration, runoff and erosion processes (Bradford et al, 1987;Mualem et al, 1993;Foley and Silburn, 2002;Assouline, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Physical soil crusts form either due to consolidation of soil material under rain impacts (structural crusts) or from the redistribution and accumulation of fine material (silica or salts) during surface runoff processes (depositional or erosion crusts) [ Ries and Hirt , ]. Because physical crusts reduce infiltration capacity locally, they contribute to increasing runoff production during moderate to heavy rainfall events [ Assouline , ; Assouline et al ., ; Belnap , ; Fearnehough et al ., ; Savenije , ; Thompson et al ., ]. In hot, arid drylands, biological soil crusts can have a similar effect, although in cooler deserts, biological crusts are also observed to enhance infiltration at the expense of surface runoff production [ Belnap , ; Issa et al ., ; Sole et al ., ; Yair et al ., ].…”
Section: Introductionmentioning
confidence: 99%